2007
DOI: 10.1111/j.1467-9280.2007.01871.x
|View full text |Cite
|
Sign up to set email alerts
|

Young Children Learning Spanish Make Rapid Use of Grammatical Gender in Spoken Word Recognition

Abstract: All nouns in Spanish have grammatical gender, with obligatory gender marking on preceding articles (e.g., la and el, the feminine and masculine forms of "the," respectively). Adult native speakers of languages with grammatical gender exploit this cue in on-line sentence interpretation. In a study investigating the early development of this ability, Spanish-learning children (34-42 months) were tested in an eye-tracking procedure. Presented with pairs of pictures with names of either the same grammatical gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
301
1
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 345 publications
(338 citation statements)
references
References 26 publications
30
301
1
6
Order By: Relevance
“…But because in these studies the most associated patient was also the most 152 associated word tout court, it remains unclear whether children were simply predicting on the 153 1 Lukyanenko and Fisher also found that 2.5-year-olds were faster to orient to a plural noun when it was heard in an informative context, a result that could also potentially be driven by prediction. However it is also explicable by facilitated integration (see also Lew-Williams & Fernald, 2007). Unambiguously predictive effects (i.e., registered before or at noun onset)…”
Section: Introduction 40mentioning
confidence: 96%
“…But because in these studies the most associated patient was also the most 152 associated word tout court, it remains unclear whether children were simply predicting on the 153 1 Lukyanenko and Fisher also found that 2.5-year-olds were faster to orient to a plural noun when it was heard in an informative context, a result that could also potentially be driven by prediction. However it is also explicable by facilitated integration (see also Lew-Williams & Fernald, 2007). Unambiguously predictive effects (i.e., registered before or at noun onset)…”
Section: Introduction 40mentioning
confidence: 96%
“…In one set of analyses, children were grouped by age (18, 24, and 36 months). In a second set of analyses, we compared children who were not yet using determiners in their own speech with those who produced determiners, given recent research showing that children's efficiency in online speech processing is associated with their level of grammatical competence (Fernald, Perfors, & Marchman, 2006;Lew-Williams & Fernald, 2007).…”
mentioning
confidence: 99%
“…Fourth, the topics of interest can be investigated under natural, relatively realistic conditions in which listeners hear words, sentences, or stories that are pragmatically relevant. A last advantage is that this technique can be used for participants of most ages, since it does not require participants to read or carry out complex tasks; it has been used very successfully with preschool children in a number of studies (e.g., Lew-Williams and Fernald 2007).…”
Section: Advantages and Challenges Of The Methodsmentioning
confidence: 99%
“…Lew-Williams and Fernald (2007) showed that the gender anticipation effect can even be found in preschoolers.…”
Section: Eye-tracking and Grammatical Processingmentioning
confidence: 99%